2001
DOI: 10.1106/cpga-20q4-yxr7-64ja
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Binding of Fresh and Stored Formulated Wheat Breads. Relationships with Dough and Bread Technological Performance

Abstract: Lipid binding in fresh and stored soured started breads formulated with nonfat [sodium carboxymethylcellulose (CMC), hydroxypropylmethylcellulose (HPMC), fungal α-amylase-and fat–monoglycerides (MGL), diacetyl tartaric acid ester of mono-diglycerides (DATEM) and sodium stearoyl lactylate (SSL)] additives were determined. Results were correlated with dough and bread technological performance during breadmaking and storage. A preferential binding of the added SSL to the starch with a concomitant displacement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 24 publications
3
40
0
Order By: Relevance
“…In the case of the inclusion of HPMC, the highest E a value obtained was potentially due to the inhibition of amylopectin retrogradation as HPMC preferential binds to starch (Collar et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…In the case of the inclusion of HPMC, the highest E a value obtained was potentially due to the inhibition of amylopectin retrogradation as HPMC preferential binds to starch (Collar et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…The addition of cellulose gum was also found to reduce the firming of the crumb during storage. Collar et al (2001) found lower firming rates in bread with added cellulose gum which may be attributed to the increase in starchy lipids through the preferential binding of cellulose gum to gluten leading to the displacement of nonstarchy lipids from the starch. Cellulose gum has also been found to counter some of the deleterious nature of freezing on frozen dough (Sharadanant and Khan, 2003).…”
Section: Breadmentioning
confidence: 95%
“…HPMC is a good gelling agent in forming intermolecularly stabilized networks, which consist of multiple polymer chains entrapping high amounts of solvents such as water (Tritt-Goc, Kowalczuk, & Pislewski, 2005). Furthermore, this polymer was shown to enhance the hydration and water binding capacities of gluten (Barcenas, De la O-Keller, & Rosell, 2009) and proposed to inhibit starch retrogradation (Collar, Martinez, & Rosell, 2001;Guarda et al, 2004). Due to these different physicochemical properties, HPMC avoids extensive moisture loss during baking and, therefore, is supposed to soften the crumb and retard staling of wheat breads.…”
Section: Relation Of Structural Features To Hydrocolloid Functionmentioning
confidence: 97%